How Do Metrics Shape Polities? From Analogue to Digital Measurement Regimes in International Health Politics - Luis Aue (International Political Sociology, 2021)
This article analyzes a historical shift from analogue to digital measurement regimes that have produced international health metrics. The historical comparative study shows that each of these measurement regimes was deeply influential in shaping the international health polity. The article conceptualizes measurement regimes based on science and technology studies as techno-social assemblages producing international health metrics. Building on polity theory, I argue that these regimes exert participation, problematization, and mode-of intervention effects in international politics. I analyze how the analogue international regime of measuring health acquired dominance after the Second World War. It built on national statistical infrastructures and international organizations and problematized international health politics as guiding nations along the development path of the Global North. It limited participation to medical and statistical experts. The digital regime—influential since the 1990s—is embedded into a private research institute and focuses on the digital recalculation of health metrics. It has shaped the field of international health politics as continuously searching for neglected problems, extended participation to a large group of passive users and supports cost-effective interventions. This article contributes conceptually and empirically to the international political sociology of health. It describes how socio-technical assemblages like measurement regimes shape international polities. – – Cet article analyse le passage historique des régimes de mesure analogiques aux régimes numériques qui ont produit des métriques de santé internationales. L'étude comparative historique montre que chacun de ces régimes de mesure a profondément façonné la politique de santé internationale. Cet article conceptualise les régimes de mesure en se basant sur des études scientifiques et technologiques en tant qu'assemblages techno-sociaux producteurs de métriques de santé internationales. Je soutiens que ces régimes exercent des effets de participation, de problématisation et de mode d'intervention dans la politique internationale en m'appuyant sur la théorie politique. J'analyse la manière dont le régime analogique international de mesure de la santé a acquis une position dominante après la Seconde Guerre mondiale. Il reposait sur des infrastructures statistiques nationales, des organisations internationales et une politique de santé internationale problématisée pour guider les nations sur la voie du développement des pays du Nord. Il limitait la participation aux experts médicaux et statisticiens. Le régime numérique, qui est influent depuis les années 90, est intégré à un institut de recherche privé et se concentre sur le recalcul numérique des métriques de santé. Il a façonné le champ de la politique internationale de santé de par sa recherche continue des problèmes négligés, son extension de la participation à un large groupe d'utilisateurs passifs et son soutien des interventions rentables. Cet article contribue conceptuellement et empiriquement à la sociologie politique internationale dans le domaine de la santé. Il décrit la manière dont les assemblages socio-techniques tels que les régimes de mesure façonnent les politiques internationales.
Keywords: 300